A Management Accounting System in an Era of Corporate Social Responsibility - Zyznarska-Dworczak, Beata (Studia Oeconomica Posnaniensia, 2014)
The purpose of this article is to present the findings of an analysis of changes in the system of management accounting in an era of corporate social responsibility. The paper indicates the need to adapt management accounting systems to the principles of socially responsible accounting adopted by an enterprise, highlighting the role of management accounting systems in meeting the information needs of the stakeholders of a socially responsible company. The article aims to analyze the impact of a company’s efforts to harmonize the implementation of economic, ecological and social objectives on its perception of cost management objectives, which determine the structure and functions of the management accounting system in a company. The analysis was conducted using descriptive and comparative methods, a literature study and an analysis of the legislation.